Phosphorus Restriction Changes the Expression of Fibroblast Growth Factor 23 and Its Receptors in Laying Hens - Ren, Zhouzheng; Yan, Jiakun; Hu, Qianli; Liu, Xinshuai; Pan, Chong; Liu, Yanli; Zhang, Xiaozhen; Yang, Xin; Yang, Xiaojun (Frontiers in Physiology, 2020)
Dietary phosphorus oversupply wastes nonrenewable natural resources and causes environmental concerns in animal agriculture. We hypothesized that laying hens don’t need large safety margins for dietary phosphorus because the existence of fibroblast growth factor 23 (FGF23). In Experiment 1, a total of 504 Hy-Line Brown laying hens (40-week-old) were randomly assigned to 7 diets (for each diet, 6 replicates of 12 hens), containing 0.12, 0.17, 0.22, 0.27, 0.32, 0.37 and 0.42% non-phytate phosphorus, respectively, for 15 weeks. In Experiment 2, a total of 14 Hy-Line Brown laying hens (40-week-old) were randomly assigned to 2 diets: 1) phosphorus restricted (n=7) diet containing 0.14% non-phytate phosphorus, and 2) regular phosphorus (n=7) diet containing 0.32% non-phytate phosphorus, for 21 days. Laying performance and egg quality were investigated in experiments 1 and 2. Phosphorus excretion and physiological changes were determined in experiment 2. As a result, dietary non-phytate phosphorus levels had no effects (P>0.05) on laying performance and egg quality in both experiments 1 and 2. In experiment 2, laying hens fed 0.14% non-phytate phosphorus had decreased phosphorus excretion (by 52.6%, P<0.001) when compared to those fed 0.32% non-phytate phosphorus. In response to the 0.14% non-phytate phosphorus diet, laying hens in experiment 2 had exhibited: 1) suppressed calvaria mRNA expressions of FGF23 (by 57.8%, P<0.001) and fibroblast growth factor receptor 1 (FGFR1, by 52.8%, P=0.012); 2) decreased serum levels of FGF23 (by 41.7%, P=0.011) and phosphorus (by 40.3%, P<0.001); 3) decreased kidney mRNA expressions of FGFR1 (by 66.0%, P=0.040) and FGFR4 (by 63.3%, P=0.012), and decreased kidney protein expression of type 2a sodium-phosphorus co-transporter (NPt2a, by 51%, P=0.025); 4) increased duodenum protein expression of NPt2b (by 45%, P=0.032); and 5) increased excretion of calcium (by 22.9%, P≤0.024). Collectively, decreasing dietary non-phytate phosphorus up to 0.12% had no negative effects on egg producing performance but significantly decreased phosphorus excretion in laying hens. The laying hens adjusted to low phosphorus diets by increasing intestinal NPt2b protein production, which was associated with decreased serum FGF23 concentration. Decreasing dietary non-phytate phosphorus is suggested to laying hen nutritionists.